Polymer modifier from vinyl ester and soybean oil derivatives: enhancing recycled asphalt and PET fiber reinforced asphalt mixture - Mingen Fei; Linli Sun; Huaye Yu; Weijian Wu; Qingbing Cai; Xiaoyan Zheng; Shuyi Wu; Xueqiang Liu; Wendi Liu; Renhui Qiu (Journal of Infrastructure Preservation and Resilience)
Abstract Reclaimed asphalt pavement (RAP) is a byproduct of transportation infrastructure construction and road maintenance. While it can be recycled by incorporating it into new asphalt mixtures, its usage is often limited due to the degraded performance of the resulting recycled asphalt mixtures including high brittleness, insufficient moisture resistance, and cracking at low temperatures. This study focuses on the development of a polymer modifier derived from vinyl ester and bio-based acrylated epoxidized soybean oil resin to facilitate the use of RAP. This modifier is specifically designed to enhance recycled asphalt binders and improve the performance of waste fiber reinforced asphalt mixtures, as verified by controlled trials. Based on resin curing and rheological analysis, the modifier underwent crosslinking during hot mixing, forming a polymer network. The rejuvenating effect of the modifier was demonstrated through Fourier transform infrared spectroscopy, gel permeation chromatography test, atomic force microscope images, and dynamic shear rheological test. The modifier dissolved the viscous asphaltenes, restoring the aged asphalt to a colloidal state and reducing its brittleness. For recycled asphalt mixtures, adjusting the asphalt to aggregate ratio to 3.5% and incorporating 0.4% fiber led to a 34.6% improvement in Marshall stability. Additionally, the presence of fibers and polymer modification strengthened the recycled asphalt mixture’s resilience to heat and moisture, improving its road performance and making it well-suited for warm and humid environments. This modifier is demonstrated to form polymer networks, restore aged asphalt binder, and address the insufficient performance of recycled asphalt mixtures.